A method for remote sensing of weak planetary magnetic fields: Simulated application to Mars. Issue 19 (1st October 2013) - Larsson, Richard; Ramstad, Robin; Mendrok, Jana; Buehler, Stefan Alexander; Kasai, Yasuko
<x xml:space="preserve">Abstract</x> [1] We present a method for characterizing the magnetic anomalies from the crustal fields in the lower atmosphere of Mars that requires two perpendicular linear polarization measurements of the Zeeman effect. The maximum effect of the magnetic field on the signal is found at the Doppler broadening width at low pressures rather than at the magnetically induced line frequency shift, and the effect strongly increases with increasing magnetic field strength. Based on simulations of the Zeeman‐affected spectral cross section of the 119 GHz O2 line in a model Martian atmosphere at various magnetic field strengths, we conclude that it should be possible to probe the strength of the magnetic anomalies remotely with presently available technology. We discuss limitations of the method, how these results could be relevant to the interpretation of residuals in Herschel/HIFI observations of Mars, as well as the application to detection of exoplanetary magnetic fields.